MENGUNGKAP RAHASIA DIBALIK ANGKA PENDAPATAN (METODE STUDI KRITIS) - Bambang Haryadi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2018)
Revenue for the company is very important. The greater income earned, the greater company's ability to fund all costs incurred. In practice, the value of income can not stand alone from the environment. This study wants to reveal the secrets behind the rising of corporate income. The paradigm used in this research is qualitative. This paradigm considers that reality is subjective and has many dimensions. The research approach uses a critical study that aims to reveal the meaning behind income numbers. This critical study is a Neo Marxist line. The results showed that: (1) the increase of income value can not be separated from the interests of management. The company's revenue value so far is a reflection of the company's strategy by using tariff increase only. Furthermore, (2) the company's revenue also shows the obligation of the company to deposit the PAD to the local government. (3) Increase in revenues has a negative impact on consumers. Increasing tariffs to earn revenue was not followed by providing good service to customers. (4) In increasing revenue, companies should not ignore environmental awareness and sustainability.